Effects of In Vivo Intracellular ATP Modulation on Neocortical Extracellular Potassium Concentration - Azin EbrahimAmini; Bojana Stefanovic; Peter L. Carlen (Biomedicines, 2022)
Neuronal and glial activity are dependent on the efflux of potassium ions into the extracellular space. Efflux of K is partly energy-dependent as the activity of pumps and channels which are involved in K transportation is ATP-dependent. In this study, we investigated the effect of decreased intracellular ATP concentration ([ATP]i) on the extracellular potassium ion concentration ([K]o). Using in vivo electrophysiological techniques, we measured neocortical [K]o and the local field potential (LFP) while [ATP]i was reduced through various pharmacological interventions. We observed that reducing [ATP]i led to raised [K]o and DC-shifts resembling spreading depolarization-like events. We proposed that most likely, the increased [K]o is mainly due to the impairment of the Na/K ATPase pump and the ATP-sensitive potassium channel in the absence of sufficient ATP, because Na/K ATPase inhibition led to increased [K]o and ATP-sensitive potassium channel impairment resulted in decreased [K]o. Therefore, an important consequence of decreased [ATP]i is an increased [K]o. The results of this study acknowledge one of the mechanisms involved in [K]o dynamics.